The Influence of Workload and Work Flexibility on Work-Life Conflict and the Role of Emotional Exhaustion - Gabriele Buruck; Anna-Lisa Pfarr; Marlene Penz; Magdalena Wekenborg; Nicole Rothe; Andreas Walther (Behavioral Sciences, 2020)
The purpose of this study is to examine the relationship between contextual work-related factors in terms of job demands (workload—WL) and job resources (work flexibility—WF), work–life conflict (WLC) and the burnout dimension emotional exhaustion (EE) in a large population-based sample. Building on the job demands resources model (JDRM), we have developed the hypothesis that WL has an indirect effect on EE that is mediated by WLC. We conducted a secondary analysis using data from the Dresden Burnout Study (DBS, N = 4246, mean age (SD) = 42.7 years (10.5); 36.4% male). Results from structural equation modelling revealed that EE is positively associated with WL (β = 0.15, p = 0.001) and negatively associated with WF (β = −0.13, p = 0.001), also after accounting for potential confounding variables (demography, depressive symptoms, and lifetime diagnosis of burnout). Both effects are mediated by WLC (β = 0.18; p = 0.001 and β = 0.08; p = 0.001, respectively) highlighting the important role of WLC in employee health. In summary, WF may help to reduce burnout symptoms in employees, whereas WL may increase them. Study results suggest that both associations depend on WLC levels.